Validity of Simple Self-Reported Periodontal Status Questions - Attawood Lertpimonchai; Supang Tuntrakul; Sasivimol Rattanasiri; Pimchanok Sutthiboonyapan; Prin Vathesatogkit; Artit Udomsak; Kanoknadda Tavedhikul (Elsevier, 2023)
ABSTRACT: Objective: The aim of this research was to evaluate the validity of the questions developed by Thai periodontists on self-reported periodontal status and symptoms in identifying severe periodontitis amongst adults in Thailand. Methods: Registered Electricity Generating Authority of Thailand (EGAT) employees completed medical examinations and full-mouth periodontal examinations. They also were interviewed using a self-reported questionnaire that was developed by Thai periodontists. The questions pertained to their periodontal status and symptoms comprising swollen gums, bad breath, loose teeth, bleeding on brushing, painful gums, and pus or abscesses. The participants were categorised as having nonsevere and severe periodontitis according to the Centers for Disease Control and Prevention in partnership with the American Academy of Periodontology (CDC/AAP) case definitions. Self-reported periodontal status and symptom results were compared with actual periodontal status. The area under the receiver operating characteristic curve (AUROCC), sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were calculated. Results: A total of 1393 EGAT employees participated in this study. The questions on self-reported periodontal status and all symptoms poorly identified patients with severe periodontitis, with an AUROCC of 0.52 to 0.60. The sensitivity was 5.0% to 40.2%; however, the specificity was good, at 73.2% to 99.1%. The validity of the self-reported questions was comparable amongst the sex, education, and income subgroups. Conclusions: This study demonstrated that self-reported periodontal status and symptoms were inadequate in identifying patients with severe periodontal disease.